2004
DOI: 10.1152/jn.00050.2004
|View full text |Cite
|
Sign up to set email alerts
|

Experience-Dependent Neural Integration of Taste and Smell in the Human Brain

Abstract: . Experience-dependent neural integration of taste and smell in the human brain. J Neurophysiol 92: 1892-1903, 2004. First published April 21, 2004 10.1152/ jn.00050.2004. Flavor perception arises from the central integration of peripherally distinct sensory inputs (taste, smell, texture, temperature, sight, and even sound of foods). The results from psychophysical and neuroimaging studies in humans are converging with electrophysiological findings in animals and a picture of the neural correlates of flavor p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

31
232
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 341 publications
(270 citation statements)
references
References 77 publications
(100 reference statements)
31
232
2
Order By: Relevance
“…f MRI provides a great tool to understand the cortical association and integration between the different modalities. Evidence from recent f MRI studies show overlapping brain responses to taste and aroma in areas including anterior insula, ACC, OFC and amygdala (43)(44)(45)(46)(47) . Verhagen and Engelen performed a meta-analysis, which suggested the anterior insula to be a multi-modal area activated by both taste and aroma stimuli (48) .…”
Section: Functional Mri Responses To Taste Aroma and Oral Somatosensmentioning
confidence: 99%
“…f MRI provides a great tool to understand the cortical association and integration between the different modalities. Evidence from recent f MRI studies show overlapping brain responses to taste and aroma in areas including anterior insula, ACC, OFC and amygdala (43)(44)(45)(46)(47) . Verhagen and Engelen performed a meta-analysis, which suggested the anterior insula to be a multi-modal area activated by both taste and aroma stimuli (48) .…”
Section: Functional Mri Responses To Taste Aroma and Oral Somatosensmentioning
confidence: 99%
“…22,62,63 Olfactory-taste convergence to represent flavour and the influence of satiety Supradditive effects indicating convergence and interactions were found for taste (sucrose) and odour (strawberry) in the orbitofrontal and ACC, and activations in these regions were correlated with the pleasantness ratings given by the participants. [64][65][66] These results provide evidence on the neural substrate for the convergence of taste and olfactory stimuli to produce flavour in humans, and where the pleasantness of flavour is represented in the human brain. McCabe and Rolls 15 have shown that the convergence of taste and olfactory information seems to be important for the delicious flavour of umami.…”
Section: Odourmentioning
confidence: 67%
“…Extant laboratory research in cognitive psychology and sensory neuroscience demonstrates enhanced multisensory integration of those sensory features that correspond crossmodally (see Parise & Spence, 2009;Spence, 2011, for a review). Enhanced multisensory integration, in turn, can result in (from a marketing perspective desirable) effects such as reduced sensory uncertainty (Munoz & Blumstein, 2012), increased attention capturing (Matusz & Eimer, 2011), and superadditive neural responses (Small, et al, 2004). Consistent with this idea, the beneficial effects of multisensory congruence on consumer preferences have been demonstrated for haptic-olfactory stimulus combinations and high-level semantic attributes (Krishna, Elder, & Caldara, 2010).…”
Section: Practical Implicationsmentioning
confidence: 88%